Uji Toksisitas Akut Fraksi Etil Asetat Batang Dan Daun Pacar Air (Impatiens balsamina Linn) terhadap Tikus Putih Betina Galur Sprague Dawley (Journal of Tropical Pharmacy and Chemistry, 2025)
Impatiens balsamina Linn has been proven through various studies to have pharmacological benefits. Yet there was no research data regarding the toxicity of these plants. The purpose of this study was to determine the acute toxicity of symptoms that occur after oral administration of ethyl acetate fraction from stems and leaves of Impatiens balsamina Linn, determine the LD50 values â€‹â€‹and toxicity category compounds in the fraction. This study employed OECD (Organization for Economic, Cooperation and Development) 425 method. Parameters observed qualitatively through the observations of the food and drink intakes and change of body everyday weight during a period of 14 days and microscopic examination of liver and kidney. The results of the study showed no symptoms of toxicity arising from qualitative observations. LD50 value of ethyl acetate fraction of stems and leaves of Impatiens balsamina Linn was more than 2000 mg/kg body weight, which belongs to moderately toxic. Also, a paired t-test concluded that there was no significant differences occuring among the amount of food and drink intakes and body weight changes before and after treatment. Likewise, based on statistical test using One Way ANOVA showed no significant difference in food intakes and body weight changes in the treatment group and control animals (p>0,05), and no significant difference of daily drinking intakes between control group and treatment group with distilled water (p>0,05). While, there was a significant difference between the control rats and the CMC treatment (p